Vegetation Structure and Composition of Coffee Agroforestry in Kalibaru District - Titanio Auditya Pribadi; Mufidah Afiyanti; Luchman Hakim (Jurnal Biodjati, 2023)
Agroforestry is a form of sustainable agriculture; the present threat of agroforestry is a change in agroforestry landforms that have switched to a less sustainable form. Coffee plays a role in the agroforestry ecosystem, Kalibaru is one of the Banyuwangi District coffee centers managed by the local community. The objective of this study was to determine the vegetation structure and analyze the effect of that on environmental parameters. Data was collected by vegetation analysis and soil parameter analysis with PAST 2020 Software version 4.05. In total, 15 research plots were used, consisting of 5 complex agroforestry, 5 simple agroforestry, and 5 monoculture plots. The results showed 20 species in complex agroforestry, 24 species in simple agroforestry, and 18 species in monoculture  were found. The highest important index level in complex agroforestry: Durio zibethinus 63.87%  for trees, the Swietenia mahagoni 64.43%  for poles, and Coffee canephora 128.87% for shrubs. In simple agroforestry : Cocos nucifera 72.83% for trees, Leucaena leucocephala  80.70%  for poles, and the Coffea canephora 137.57%  for shrubs. In monoculture agroforestry: Hibiscus similis 82.99%  for trees, Leucaena leucocephala 209.22% for poles, and Coffea canephora 130.96% for shrubs. Agroforestry in Kalibaru was categorized  in the moderate diversity. The diversity index (H') in complex agroforestry showed H' trees 2.21, pole 2.03 and. shrubs 1.60. Simple agroforestry shows H' tree 2.00, pole 2.49, and shrubs 1.50. Monoculture shows H' tree 1.98, pole 0.64, and shrubs 1.54. Agroforestry a role in maintaining soil moisture and temperature, complex agroforestry: temperature 24 0C, and Moist 5.82, simple: temperature 24.2 0C, Moist 5.42, and Monoculture temperature 26 0C, Moist 4.54.